ANALISIS KEGIATAN BIMBINGAN BELAJAR PADA ANAK USIA DINI DALAM KREATIVITAS PEMBELAJARAN FINGER PAINTING (Melukis Terhadap Peningkatan Motorik Halus) - Sandi, Noviea Varahdilah; Setyorini, Ririn (Generasi Emas, 2018)
This research analyzes the learning of color game and painting concept by using Finger Painting, this study also analyzes early childhood creativity in playing their imagination. The design of this research is qualitative research and using the descriptive method, which is to study and describe the fine art learning by seeing a child’s creativity through their soft motoric skill in learning Finger Painting. The technique of collecting data is done by observation, documentation, and interview. The subject of this research focused on early childhood which follows ‘Rumah Pintar’ tutoring activity in Bandung district. The result of the research showed that: 1) Children that joint on tutoring activity have enthusiast in learning.  2). When painting, they prefer using their imagination (they don’t paint what they look, 3). Children’s creativity increases in mixing many kinds of tint. 4). The success of painting creativity achieved, 5). There is an effect of learning finger painting activity to the enhancement of children’s soft motoric